Cleavage of the dimeric heterometallic complexes [Pd(dppf)(μ-Cl)]2[BArF24]2 (dppf = 1, 1′-bis(diphenylphosphino)ferrocene, BArF24 = tetrakis(bis-3, 5-trifluoromethylphenyl)borate) via addition of monodentate phosphine ligands. (1st August 2022) - Wolfarth, Sadie A.; Colicchio, Nick G.; Nataro, Cassie S.; Reinheimer, Eric W.; Nataro, Chip
Graphical abstract: Reaction of the dimer, [Pd2 (dppf)2 (μ-Cl)2 ][BArF24 ]2 (dppf = 1, 1ʹ-bis(diphenylphosphino)ferrocene; BArF24 = tetrakis(3, 5-bis(trifluoromethyl)phenyl)borate) with monodentate phosphines (PPh3, PMe3 or PPh2 Fc) results in formation of [Pd(dppf)(PR3 )Cl][BArF24 ]. The compounds were characterized by NMR, X-ray crystallography and cyclic voltammetry. Abstract: The cleavage of the heterometallic, chloro-bridged dimer [Pd2 (dppf)2 (µ-Cl)2 ][BArF24 ]2 (dppf = 1, 1′-bis(diphenylphosphino)ferrocene; BArF24 = tetrakis(3, 5-bis(trifluoromethyl)phenyl)borate) was of interest within this study. The addition of the monodentate phosphines, PPh3, PMe3 and diphenylferrocenylphosphine (PPh2 Fc), resulted in the formation of three new [Pd(dppf)(PR3 )Cl][BArF24 ] complexes. These new compounds were characterized by NMR and the X-ray crystal structures of all three compounds were obtained. Structural parameters for these compounds were compared to other square-planar Pd(II) compounds with a dppf ligand. In addition, the oxidative electrochemistry of these three compounds was examined using cyclic voltammetry and the electronic communication between the two different iron centers in [Pd(dppf)(PPh2 Fc)Cl][BArF24 ] was explored.